The Effect of Marketing Mix on Satisfaction and Its Implications for Visitor Loyalty - Rita Zahara (Dinasti Publisher, 2024)
The purpose of this study was to determine and analyze: Marketing Mix on Satisfaction and its implications on Visitor Loyalty a survey of visitors at Alamendah Tourism Village, Rancabali District, Bandung Regency), both simultaneously and partially. The research method used in this research is descriptive and verification method, the unit of analysis in this research is the visitors in A;amendqah Tourism Village, Rancabali District, Bandung Regency with a sample of 30 people. And the analysis method used is quantitative analysis and path analysis. Based on the results of the study, it was found that the marketing mix on satisfaction and its implications on visitor loyalty visitor surveys at Alamendah Tourism Village, Bandung Regency can generally be said to be good, the marketing mix at Alamendah Tourism Village, Bandung Regency is currently considered good. The marketing mix simultaneously affects visitor satisfaction at Alamendah Tourism Village, Bandung Regency. However, partially visitor satisfaction dominantly affects visitor loyalty than the marketing mix. Because satisfaction dominantly affects visitor loyalty, the first priority in improving the marketing mix at Alamendah Tourism Village, Bandung Regency is expected to remain consistent in maintaining existing conditions, thereby increasing the quality of comprehensive visits/tourists.